2003
DOI: 10.1007/bf02703323
|View full text |Cite
|
Sign up to set email alerts
|

A comparative machining study of diamond-coated tools made by plasma torch, microwave, and hot filament techniques

Abstract: An effective metal-cutting tool is usually a combination of a hard coating and a tough substrate. The successful deposition of diamond outside its thermodynamic stability range has stimulated the development of a new class of cutting tools: those with diamond-coated inserts of any desired style and edge geometry. The successful implementation of diamond coatings also expedited similar research in the deposition of cubic boron nitride. This paper presents superhard coating tools, with emphasis on diamond-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…55 In this study, 55 horse and pig neutrophils were exposed to urea, apatite hydroxyl, and pyrophosphate. The results demonstrated that they induced superoxide and peroxide at the same viscosity and temperature, but exposing the neutrophils to the diamond crystal did not cause this effect at 37°C.…”
Section: Nanodiamond Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In this study, 55 horse and pig neutrophils were exposed to urea, apatite hydroxyl, and pyrophosphate. The results demonstrated that they induced superoxide and peroxide at the same viscosity and temperature, but exposing the neutrophils to the diamond crystal did not cause this effect at 37°C.…”
Section: Nanodiamond Particlesmentioning
confidence: 99%
“…The monocyte morphology changed after silicon carbide and HA digestion, but no differences were seen after diamond absorption. 55 …”
Section: Nanodiamond Particlesmentioning
confidence: 99%